1991
DOI: 10.1523/jneurosci.11-05-01173.1991
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin I and Synaptophysin expression during ontogenesis of the mouse peripheral vestibular system

Abstract: Synapsin I and Synaptophysin are selectively localized in axonal endings of CNS neurons where they are associated with small synaptic vesicle membranes. The development of expression of these 2 proteins was studied by immunocytochemistry during ontogenesis of the peripheral vestibular system in the mouse. Both proteins are localized in vestibular ganglion neurons and in their peripheral sensory extensions as early as gestational day 14. While the entire periphery of these fibers is labeled during embryogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…Studies on the developmental expression of synaptophysin and synaptoporin in the central nervous system revealed that these proteins are present not only in mature terminals but also in outgrowing axons (Bergmann et al, 1991Scarfone et al, 1991;Ovtscharoff et al, 1993; this study) and, unexpectedly, in the cytoplasmic bridge connecting retinal photoreceptor cell bodies with the rod component (Schmied and Holtzman, 1989), in dendrites of the continuously regenerating olfactory receptor neurons and, transiently, in dendrites of developing hippocampal pyramidal neurons (this study). While synaptic vesicles in outgrowing axons could serve as a reservoir for subsequent synaptogenesis, synaptic vesicle membrane antigens in developing dendrites are unlikely to contribute to synaptic organelles.…”
Section: Discussionmentioning
confidence: 58%
“…Studies on the developmental expression of synaptophysin and synaptoporin in the central nervous system revealed that these proteins are present not only in mature terminals but also in outgrowing axons (Bergmann et al, 1991Scarfone et al, 1991;Ovtscharoff et al, 1993; this study) and, unexpectedly, in the cytoplasmic bridge connecting retinal photoreceptor cell bodies with the rod component (Schmied and Holtzman, 1989), in dendrites of the continuously regenerating olfactory receptor neurons and, transiently, in dendrites of developing hippocampal pyramidal neurons (this study). While synaptic vesicles in outgrowing axons could serve as a reservoir for subsequent synaptogenesis, synaptic vesicle membrane antigens in developing dendrites are unlikely to contribute to synaptic organelles.…”
Section: Discussionmentioning
confidence: 58%
“…The new neurons appeared to have some properties of presynaptic neurons during synaptogenesis: the expression of synaptic markers was localized to the neuronal side at the actual contact with the hair cell (Martinez-Monedero et al, 2006). The processes of spiral ganglion neurons that extend to hair cells during development stain for synapsin and synaptophysin (Scarfone et al, 1991) and it is possible that the identity of this peripheral process as a dendrite is only acquired after it forms a connection to the hair cell. Neurite outgrowth has been shown to occur before the identity of axons and dendrites is specified.…”
Section: Formation Of Inner Ear Cells From Endogenous Stem Cellsmentioning
confidence: 99%
“…synaptophysin, and semiquantitative immunohistochemical techniques, to obtain an efficient panoramic view of the sensory organ innervation [Scarfone et al, 1988[Scarfone et al, , 1991. Synaptophysin is a 38000-dalton integral protein membrane present in vesicles thought to be involved in the release of neurotransmitter and trophic peptides in different regions of the central nervous system [Greengard et al, 1993;Jahn et al, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…In the vestibular and auditory sensory epithelia, synaptophysin immunohistochemistry has been used as a marker for synaptogenesis during development of the inner ear [Sans and Scarfone, 1996;Scarfone et al, 1991;Sokolow-Lopez/Ayala/Honrubia ski and Cunningham, 1999]. In the vestibular organs of adult animals, immunoreactivity to this protein is found in the cytoplasm of hair cells, efferent vestibular nerve endings and also postsynaptically in the neck of the afferent calyces [Dechesne et al, 1997;Scarfone et al, 1988Scarfone et al, , 1991.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation